Comparison of propeller perforator flap and venous supercharged propeller perforator flap in reconstruction of lower limb soft tissue defect: A prospective study. Issue 2 (17th March 2017) - Chaput, Benoit; Bertheuil, Nicolas; Grolleau, Jean‐Louis; Bekara, Farid; Carloni, Raphael; Laloze, Jerome; Herlin, Christian
Abstract : Introduction: In lower limbs, reliability of propeller perforator flaps (PPF) remains uncertain. The main complication is venous congestion, which can lead to distal necrosis. We aim to highlight if venous supercharging of PPF could substantially limit complications in lower limb coverage. Methods: Between 2011 and 2016, we developed a standardized procedure of venous supercharging in the lower limb reconstruction with PPF using saphenous veins anastomosis. Then, we prospectively compared a consecutive series of 30 PPF to cover lower limbs defect, with a consecutive series of 30 venous‐supercharged PPF (vsPPF). Etiologies of trauma, flap harvesting, complications, and outcomes were compared. Results: The etiologies of the defect were acute trauma in 67.6% of reconstruction with PPFs and 60% of reconstruction with vsPPFs ( P = 0.826). The average size of the skin paddle was 48.1 ±18.2 cm 2 for PPF and 58.9 ±19.5 cm 2 for vsPPF, and the average arc of rotation was 126.7° ±33.1 for PPF and 121.3° ±31.9 for vsPPF. The average sizes and rotation arcs between the two flaps were not significantly different ( P = 0.031, P = 0.527). The operative time was significantly increased for vsPPF when compared to PPF procedure (128.8 ±8.5 minutes vs. 81.3 ±10.1 minutes, P < 0.001). Venous congestion was significantly higher in PPF with 11 cases than in vsPPF with two cases (36.7% versus 6.7%, P = 0.010). Distal necrosis were significantly higher in PPF with nine cases than in vsPPF with 1 cases (30% versus 3.3%, P = 0.012). Following poor flap evolution, stitches removal was significantly more frequent in PPF with 11 cases than in vsPPF with one case (36.7% vs 3.3%, P = 0.002). Leeches application was significantly more frequent for PPF procedures with nine cases, than for vsPPF with one case (30% vs 3.3%, P = 0.012). The average length of hospital stay for PPF was significantly longer than for vsPPF (8.78 versus 7.11 days, P = 0.026). Conclusion: The vsPPF is a reliable alternative to PPF to cover small‐ and medium‐size defect in lower limbs, reducing venous congestion and overall complications.